2015
DOI: 10.1016/j.nimb.2014.11.097
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of He clusters by inert-gas impurities in tungsten: First-principles predictions and experimental validation

Abstract: a b s t r a c tProperties of point defects resulting from the incorporation of inert-gas atoms in bcc tungsten are investigated systematically using first-principles density functional theory (DFT) calculations. The most stable configuration for the interstitial neon, argon, krypton and xenon atoms is the tetrahedral site, similarly to what was found earlier for helium in W. The calculated formation energies for single inert-gas atoms at interstitial sites as well as at substitutional sites are much larger for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 32 publications
7
25
1
Order By: Relevance
“…The interaction of solute atoms with inert gas atoms [136] and possible impurities in the W matrix has also been investigated [10,128] C binds very strongly with both the vacancy and the SIA, and so does H. The binding energy of an SIA with H is not negligible: 0.20 eV, and the binding energy of a vacancy with H is high: 1.43 eV [138], In a previous work, it was shown that H binds also very strongly with He clusters [139], in agreement with the experimental findings that He pre-irradiation of metals efficiently enhances the retention of hydrogen isotopes in the penetrated region. Mo does not appear to establish any interactions with vacancies, contrarily to Re whose binding energy with the vacancy is around 0.2 eV.…”
Section: Point Defects In Pure Wmentioning
confidence: 99%
“…The interaction of solute atoms with inert gas atoms [136] and possible impurities in the W matrix has also been investigated [10,128] C binds very strongly with both the vacancy and the SIA, and so does H. The binding energy of an SIA with H is not negligible: 0.20 eV, and the binding energy of a vacancy with H is high: 1.43 eV [138], In a previous work, it was shown that H binds also very strongly with He clusters [139], in agreement with the experimental findings that He pre-irradiation of metals efficiently enhances the retention of hydrogen isotopes in the penetrated region. Mo does not appear to establish any interactions with vacancies, contrarily to Re whose binding energy with the vacancy is around 0.2 eV.…”
Section: Point Defects In Pure Wmentioning
confidence: 99%
“…Tungsten has been investigated extensively by first-principles calculations, 1-29 including the energetics and kinetics of vacancy and interstitial 2, 3,5,7,8,23,26,27 , the energetics and kinetics of Helium 6,7,[9][10][11][12] , Ar/Ne/Kr/Xe 28,29 , and Hydrogen 10,12,[15][16][17][18]20,29 , Hydrogen and vacancies 10,12,18 , and the solute−point defect interactions 19,22 . The interaction of vacancies has been investigated 4,7,8,21 , whereas the interaction of self-interstitials in W has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…3) Studies on tungsten receive an increasing amount of attention from scientists and engineers. [4][5][6][7][8][9][10] Tungsten is subjected to high particle fluxes in fusion reactors, not only the plasma background ions (H, D and T) but also the intrinsic impurities (He, Be and C). 11,12) Because hydrogen is one of the major plasma background ions, hydrogen (H) irradiation may result in the change of the mechanical properties of tungsten.…”
Section: Introductionmentioning
confidence: 99%
“…A number of experimental and theoretical studies were carried out to understand the interaction between the hydrogen or helium impurity and the tungsten host lattice. 1,7,8,[20][21][22][23][24][25][26][27][28][29] For example, Arkhipov et al found that hydrogen could form a blister on the tungsten surface. 20) Ye et al presented the experimental results in a divertor plasma simulator NAGDIS-II and observed the formation of hydrogen bubbles on the surface of tungsten.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation